Spatial scalable video coding and transmitting system - Gao, Xiang (2008)
This thesis described the design and implementation of the Spatial Scalable Video Coding and Transmitting System (SSVCTS) based on MPEG-4 standard that involves the processing of Video Object Planes (VOPs).